Answer:
![x= 3+√(2), \quad x= 3 -√(2)](https://img.qammunity.org/2023/formulas/mathematics/college/k2gkccmj4gzz1cfuuvubcpigol4kz26wr3.png)
Explanation:
Given quadratic equation:
![y = x^2 - 6x+7](https://img.qammunity.org/2023/formulas/mathematics/college/weie8fw6mdb7ag3oterc0g1agg2ul8wo9t.png)
To complete the square, begin by adding and subtracting the square of half the coefficient of the term in x:
![\implies y = x^2 - 6x+\left((-6)/(2)\right)^2-\left((-6)/(2)\right)^2+7](https://img.qammunity.org/2023/formulas/mathematics/college/qqy4w4lap1k878eyke64fz20xsaj4k3byr.png)
![\implies y = x^2 - 6x+\left(-3\right)^2-\left(-3\right)^2+7](https://img.qammunity.org/2023/formulas/mathematics/college/c4zmpjqlb5lockw0kavbdm4bu6o3pzxd98.png)
![\implies y = x^2 - 6x+9-9+7](https://img.qammunity.org/2023/formulas/mathematics/college/p7p3clb3z5xcqu80x628iup24axhewnl8g.png)
Factor the perfect square trinomial:
![\implies y=(x-3)^2-9+7](https://img.qammunity.org/2023/formulas/mathematics/college/gtxm5p48u1yfzluimugq3zwzy3v5vractx.png)
![\implies y=(x-3)^2-2](https://img.qammunity.org/2023/formulas/mathematics/college/6b4ktbguds58hmqcmawqtoliwbkheyli08.png)
To solve the quadratic, set it to zero and solve for x:
![\implies (x-3)^2-2=0](https://img.qammunity.org/2023/formulas/mathematics/college/9z7ihpm54adzyq3sxqqi60t6iymlotpsj3.png)
![\implies (x-3)^2-2+2=0+2](https://img.qammunity.org/2023/formulas/mathematics/college/fmbz05len7xy0gmcndg0urwmpqz6fiivt3.png)
![\implies (x-3)^2=2](https://img.qammunity.org/2023/formulas/mathematics/college/prsxpg54a53g0oowu47s2ay5dvpql7u53l.png)
![\implies √((x-3)^2)=√(2)](https://img.qammunity.org/2023/formulas/mathematics/college/h3mn9tpfrxur6c6wu0n3gmrh9wwm5m8nln.png)
![\implies x-3= \pm√(2)](https://img.qammunity.org/2023/formulas/mathematics/college/vj2jv5zz7dfpqbqolesd5h69eqd8ipa3cy.png)
![\implies x-3+3= 3\pm√(2)](https://img.qammunity.org/2023/formulas/mathematics/college/9sgiqls76qiqp245aoejv2rqh6w3ic15a8.png)
![\implies x= 3\pm√(2)](https://img.qammunity.org/2023/formulas/mathematics/college/52ft2mysvxgpkau3ibbjfthhqn8t9k3nq7.png)
Therefore, the solution to the given quadratic equation is:
![x= 3+√(2), \quad x= 3 -√(2)](https://img.qammunity.org/2023/formulas/mathematics/college/k2gkccmj4gzz1cfuuvubcpigol4kz26wr3.png)